A carvacrol–thymol blend decreased intestinal oxidative stress and influenced selected microbes without changing the messenger RNA levels of tight junction proteins in jejunal mucosa of weaning piglets. (15th July 2016) - Wei, H.-K.; Xue, H.-X.; Zhou, Z. X.; Peng, J.
Abstract : Recent studies indicate that intestinal oxidative stress and microbiota imbalance is involved in weaning-induced intestinal dysfunction in piglets. We have investigated the effect of feeding a carvacrol–thymol blend supplemented diet on intestinal redox status, selected microbial populations and the intestinal barrier in weaning piglets. The piglets (weaned at 21 days of age) were randomly allocated to two groups with six pens per treatment and 10 piglets per pen. At weaning day (21 days of age), six piglets were sacrificed before weaning to serve as the preweaning group. The weaned group was fed with a basal diet, while the weaned-CB group was fed with the basal diet supplemented with 100 mg/kg carvacrol–thymol (1 : 1) blend for 14 days. On day 7 post-weaning, six piglets from each group were sacrificed to determine intestinal redox status, selected microbial populations, messenger RNA (mRNA) transcript levels of proinflammatory cytokines and biomarkers of intestinal barrier function. Weaning resulted in intestinal oxidative stress, indicated by the increased concentration of reactive oxygen species and thiobarbituric acid-reactive substances present in the intestine. Weaning also reduced the population of Lactobacillus genus and increased the populations of Enterococcus genus and Escherichia coli in the jejunum, and increased mRNA levels of tumor necrosis factor α (TNF- α ), interleukin 1 β and interleukin 6 (IL-6). In addition, decreased mRNA levels of zonula occludens and occludin in the jejunal mucosa and increased plasma diamine oxidase concentrations indicated that weaning induced dysfunction of the intestinal barrier. On day 7 post-weaning, supplementation with the carvacrol–thymol blend restored weaning-induced intestinal oxidative stress. Compared with the weaned group, the weaned-CB group had an increased population of Lactobacillus genus but reduced populations of Enterococcus genus and E. coli in the jejunum and decreased mRNA levels of TNF- α . The results indicated that weaning induced intestinal oxidative stress and dysfunction of the intestinal barrier. Dietary supplementation with 100 mg/kg carvacrol–thymol (1 : 1) decreased the intestinal oxidative stress and influenced selected microbial populations without changing the biomarkers of intestinal barrier in weaning piglets.